Face Validity for Early Literacy Skills Indicators from Educators’ Perspective - Juppri Bacotang; Siti Farhana Md. Yasin; Rashidin Idris; Adibah Abdul Latif; Muhamad Suhaimi Taat; Connie Shin @ Connie Cassy Ompok; Nur Suhaidah Sukor; Saturia Amiruddin; Ratin Wahyu Juni Atma (Human Resource Management Academic Research Society, 2024)
The purpose of this study was to determine the face validity of the Early Literacy Skills Indicators (ELSI), which are used to measure the early literacy skills of children aged 3 to 4. To achieve face validity for ELSI, the researchers conducted a descriptive survey of 21 educators. The researchers provided each educator with the Face Validity Questionnaire (Educator) and a complete copy of the ELSI, which included various media, including (i) the ELSI Handbook, (ii) the "Ta Ta House" Storybook, (iii) the Children Score Record Form, and (iv) the ELSI Microsoft Excel. Each educator was responsible for analysing all ELSI media for language, space and font size, clarity, and appropriateness in measuring children's early literacy skills. The study findings suggested that ELSI's face validity extended to all of these mediums. This suggests that ELSI has a high level of face validity when measuring children's early literacy skills. Thus, educators can utilise ELSI to assess the early literacy skills of children aged 3 to 4.